PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MINAT BACA SISWA MELALUI PERPUSTAKAAN SEKOLAH - Sriwahyuni, Eci (Graduate Program Magister Manajemen Pendidikan, 2018)
The reading interest of Indonesian people still low compared from other countries. It needs to introduce the love of reading early, so the children will have long life reading interest. In this case the school’s library should be able to nurture students into a reading society. This research is qualitative with key informant is principal and supporting informant are librarian, teachers and students of State Primary School 31 of Balai Labuh Bawah. The data were collected by using observation, interview and documentation. The results showed that the principal play an active role to increase students' reading interest through the school’s library. The role of principals are (1) increasing the students reading interest through exemplary; (2) utilizing the school’s library as a learning resource; (3) giving reward to the students who frequently visit and borrow books in school’s library; (4) increasing the books collection in school’s library; (5) making the school’s library as a convenient place for reading activities; and (6) fostering librarians through upgrading and seminar activities.